Pengaruh Metode Tafsir dalam Meningkatkan Kemampuan Membaca Al-Qur'an Santri Rumah Mengaji Pondok Pasjava Medan - Sri Wulan Dari; Zailani Zailani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The objective of this research is to examine how employing the tafsir methodology affects the proficiency in Qur'anic recitation demonstrated by attendees at the Pondok Pesantren Medan Reciting Center. Adopting a quantitative framework utilizing a descriptive-correlational design, this investigation will quantify the association and effect stemming from the implementation of the tafsir method on the pupils' level of Qur'an reading competence. Participants in this investigation comprise currently enrolled students at the facility who possess foundational skills in reading the Qur'an but encounter difficulties regarding reading speed, accurate articulation of sounds (makhraj), and correct execution of the rules of recitation tajweed. Data was collected through a Likert scale closed questionnaire that captured students' learning experiences with their interpretation methods and Qur'an reading skills. The data were analyzed using SPSS software, which included validity, reliability, normality, linearity, Pearson correlation, simple linear regression, and partial t-test. The results of the study show that the tafsir method makes a positive contribution in improving students' Qur'an reading ability. Integrating the explanation of verse meaning into the learning process supports smoother reading, more precise pronunciation of letters, and better application of tajweed. Thus, the tafsir method serves as an effective teaching strategy to improve the quality of students' Qur'an reading ability.